Conservation Challenges for Olive Ridley Sea Turtles in North Kerala: A Case Study of Kolavipalam Beach - M. P, Nasja.; Babu, Dinesh; I. P, Abdul Razak. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The Indian coastal regions harbor diverse species of sea turtles, among which Olive Ridley turtles are prevalent and commonly encountered in the coastal waters of Kerala and the Lakshadweep Islands. These turtles exhibit a preference for nesting on expansive beaches and sandy areas situated at river mouths. Our study area, located in the Irringal village of Kozhikode district in North Kerala, overlooks the Arabian Sea and lies adjacent to the Kottapuzha River. Here, the local community has undertaken a conservation initiative known as Theeram Prakriti Samrakshana Samithi (TPSS) to safeguard Olive Ridley turtles during their nesting period. During this study, we investigated the status of Olive Ridley turtle nesting grounds and populations in Kolavipalam surveying beach from 2019 to 2023. We recorded the number of OliveRidley sea turtle nestings during this period, collected the eggs, and assessed the hatching success from the artificial hatchery. The mean annual number of eggs hatched was 54.4 ± 23.27 and the overall nesting success was 25.73%. The study revealed a significant decline in nesting turtles compared to previous years, with only 1-2 egg-laying turtles observed yearly. Median hatch success declined dramatically from 80.21% during the earlier period to 36.41% during this study period. Our analysis identified various challenges affecting turtle nesting, including the construction of sea walls, the development of beach areas for tourism, and changes in rainfall patterns. As a result, turtles were forced to nest closer to the shoreline, making their nests more vulnerable to waves and flooding. These findings emphasized the urgent need for increased conservation efforts to safeguard these endangered sea turtles, particularly in areas like Kolavipalam, which were once ideal nesting sites.